THEORETICAL FUNDAMENTALS OF STUDENT TRAINING TO CREATIVE PROFESSIONAL ACTIVITY IN CONDITIONS OF PEDAGOGICAL UNIVERSITY BY MEANS FOREIGN LANGUAGE (Pedagogy of Higher and Secondary Education, 2022)
This article deals with the question of formation of student creative abilities. The author shows the specific conditions to for students’ creative abilities at schools of higher learning.